Species Specific Responses to Grazer Cues and Acidification in Phytoplankton- Winners and Losers in a Changing World - Rigby, Kristie; Kinnby, Alexandra; Grønning, Josephine; Ryderheim, Fredrik; Cervin, Gunnar; Berdan, Emma L.; Selander, Erik (Frontiers in Marine Science, 2022)
Phytoplankton induce defensive traits in response to chemical alarm signals from grazing zooplankton. However, these signals are potentially vulnerable to changes in pH and it is not yet known how predator recognition may be affected by ocean acidification. We exposed four species of diatoms and one toxic dinoflagellate to future pCO2 levels, projected by the turn of the century, in factorial combinations with predatory cues from copepods (copepodamides). We measured the change in growth, chain length, silica content, and toxin content. Copepodamides induced toxin production, and chain length shortening which was largely unaffected by increased pCO2. Effects of increased pCO2 were highly species specific. The induction of defensive traits was accompanied by a significant reduction in growth rate in three out of five species. The reduction averaged 39% and we interpret this as an allocation cost associated with defensive traits. Copepodamides induced significant chain length reduction in three of the four diatom species. Under elevated pCO2 Skeletonema marinoi reduced silica content by 30% and in Alexandrium minutum the toxin content was reduced by 30%. Using copepodamides to induce defensive trait in the absence of direct grazing provides a straightforward methodology to assess costs of defence in microplankton. We conclude that copepodamide signalling system is likely robust to ocean acidification. Moreover, the variable responses of different taxa to ocean acidification suggest that there will be winners and losers in a high pCO2 world, and that ocean acidification may have structuring effects on phytoplankton communities.